SPECIAL ASPECTS OF THE SECOND FOREIGN LANGUAGE TEACHING AT THE BASIC COURSE - Avdienko, Irina; Zhukova, Kateryna; Kotova, Anna; Rudaya, Nataliya; Kholodniak, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The aim of this work is to define special aspects of the second foreign language (SFL) grammar teaching at the basic course, because at Ukrainian universities the number of course hours for studying of the SFL is less than for the first one. This leads to more superficial learning of grammar material. In addition, it was believed that the grammar of the SFL can be taught in the context of the general course. The integration of vocabulary and grammar teaching hampered the thorough understanding of grammatical constructions by the students, as the study of the SFL came against the background of the first foreign language enhanced studying. For the scientific analysis of this issue, the methods of causality analysis and generalization were applied, which helped identify the priority of the communicative approach in the SFL grammar teaching, as this approach develops the oral and written skills of students. Nevertheless, there are some factors that impede the fluency of grammar material at the basic course of education. The article reveals problems and ways to solve them during the training. The authors consider that the communicative approach in the SFL grammar teaching will help master the language more quickly and efficiently, which meets the needs of modern society.